Exploration Of English Switching Codes In Teil Course Discussions - Febi Frisca Novanti; Aida Nur Amalina; Nazwa Yuki Nabila; Aidil Syahputara (CV. ITTC INDONESIA, 2026)
This study aims to explore the practice of English code-switching in discussions in the Teaching English as an International Language (TEIL) course in the university environment. This study uses a descriptive qualitative approach to examine the form and function of code-switching as a communicative strategy in the context of multilingual learning. The research data was collected through video recordings of Zoom-based class discussions, student questionnaires, and supporting documentation in the form of Semester Learning Plans (RPS) and lecture materials. The verbal data obtained is transcribed and analyzed thematically to identify the context and purpose of using code-switching. The results of the study show that code-switching is used by students to (1) clarify understanding of theoretical concepts, (2) maintain the continuity of academic communication, (3) affirm critical opinions or attitudes, and (4) build solidarity and comfort in discussions. These findings indicate that code-switching does not solely reflect linguistic limitations, but rather is a communicative strategy that is in line with the principles of Teaching English as an International Language (TEIL) and English as a Lingua Franca (ELF). Therefore, this study emphasizes the importance of applying a more inclusive and contextual pedagogical approach to multilingual practices in English learning in higher education.